PENGARUH MEDIA SOSIAL, KEPERCAYAAN, DAN PERSEPSI MANFAAT TERHADAP KEPUTUSAN PEMBELIAN ONLINE - Siti Maisaroh; Totok Wibisono (Universitas Ahmad Dahlan, 2022)
The purpose of this study was to analyze the influence of social media, trust, and perceived benefits to purchasing decisions on the Blibli.com online platform. The population of this study is consumers of the Blibli.com online platform in Indonesia. By using the purposive sampling method, this research used 96 consumers as a sample of respondents. The primary data from respondents are gathered by distributing a questionnaire to the respondent. The gathered data then was analyzed by using multiple regression analysis. The results of this study showed that Social media has an effect on Purchase Decisions, Trust has an effect on Purchase Decisions, and Perceived value has an effect on Purchase Decisions.